Flying-fox species and Hendra virus spillover risk: comment on 'Factors explaining the dispersal of Hendra virus disease in South-East Queensland' by Burnham and Chong (2016). Issue 6 (3rd June 2017) - Field, Hume; Edson, Dan; Smith, Craig
Abstract: The approach taken by Burnham and Chong to explain the occurrence of Hendra virus incidents in Australia, while analytically valid, is compromised by erroneous and incomplete biological data underpinning the analyses. Firstly, they erroneously state the peak mating, pregnancy and birthing periods in black, grey-headed and little red flying-foxes, thus their related interpretations and conclusions are flawed. Secondly, the reported association between grey-headed flying-fox density and HeV incidents is at odds with recent findings suggesting grey-headed flying-foxes are an insubstantial host. While this broader epidemiological perspective was not within their stated aims, it is appropriate that it be canvassed in discussion of their geo-spatial analyses given the level of horse-industry, public and media interest in Hendra virus and the potential for confusion and mixed messages regarding HeV exposure risk management. We suggest that a broader collaborative cross-disciplinary approach offers synergies that produce robust, real-world 'one health' outputs.